Report of the Working Group on Land Reclamation and Development for Formulation of the Seventh Five Year Plan (1985-90) - Planning Commission (Planning Commission, 1985)
The Planning Commission, vide their office memorandum No. M-12043/3/83-Agri. dated 26th October, 19t3 constituted a Working Group on Land Reclamation at Development for formulation of the Seventh Five Year Plan under the chairmanship of Dr. K.C S. Acharya, Additional Secretary in the Department of Agriculture & Cooperation with Shri A.C. Garg, Joint Commissioner (Projects), Department of Agriculture & Cooperation as the member-secretary. The composition of the Working Group is given in Appendix-I. Subsequently, vide their Office Memorandum of even number dated 30th November, 1983, the Planning Commission included Joint Secretary (Plan Finance), Ministry of Finance and Joint Secretary (SC) and Land Resources Commissioner, Department of Agriculture and Cooperation as members of the Working Group On a suggestion from the Ministry of Home Affairs, it was decided to include Shri R.K. Saiyed, Additional Secretary in the Ministry of Home Affairs as a member of the Working Group vide Ministry of Agriculture No. 14-13/83-STS (O-ES) dated 7th August, 1984.
Ministry of Agriculture Department of Agriculture and Cooperation Soil and Water Conservation Division
Ministry of Agriculture Department of Agriculture and Cooperation Soil and Water Conservation Division